Marine energy harvesting from fluid flow via vortex induced vibrations - Zahrapanah Razaviyn; Milad Heidari; Sivasakthivel Thangavel; Vikas Verma; Ashwani Kumar; Ashok Kumar Yadav (International Journal of Thermofluids)
This research study highlights into the dynamics of vortex-induced vibrations (VIV) in a rigid cylinder, employing computational fluid dynamics (CFD) simulations validated against experimental data. The primary objective is to explore the potential of harnessing energy from fluid flow-induced vibrations, particularly at lower flow speeds, which are traditionally overlooked by conventional turbine technologies. The CFD simulations investigated the transverse vibrations of a rigid cylinder with elastic support across a wide range of Reynolds numbers. The numerical results were compared with experimental data obtained from the University of Michigan, demonstrating strong correlation, especially for a spring stiffness of 1200 N/m, zero damping, and a relative mass of 1.89. Under these conditions, the maximum relative amplitude of 1.75 was achieved at a Reynolds number of 90,000. The study revealed that increasing spring stiffness up to 1200 N/m enhances the oscillation amplitude. However, further increases in stiffness lead to a decrease in amplitude. Damping and relative mass also significantly influence the vibration behavior. Lower relative masses and damping ratios result in larger amplitude oscillations over a broader range of Reynolds numbers. These findings underscore the feasibility and potential of energy extraction from fluid flows that were previously considered unsuitable. The quantitative insights provided in this study offer valuable guidance for the design and optimization of VIV energy converters. Future research should focus on long-term simulations to further elucidate the impact of these parameters on the performance and durability of such systems.